In vitro neurotoxicity of salsolinol is attenuated by the presynaptic protein α-synuclein - do Carmo-Gonçalves, Phelippe; Coelho-Cerqueira, Eduardo; Cortines, Juliana R.; de Souza, Theo Luiz Ferraz; Romão, Luciana; Follmer, Cristian (Biochimica et biophysica acta. General subjects, 2018)
Salsolinol (SALSO), a product from the reaction of dopamine (DA) with acetaldehyde, is found increased in dopaminergic neurons of Parkinson's disease (PD) patients. The administration of SALSO in rats causes myenteric neurodegeneration followed by the formation of deposits of the protein α-synuclein (aS), whose aggregation is intimately associated to PD. NMR, isothermal titration calorimetry and MS were used to evaluate the interaction of SALSO with aS. The toxicity of SALSO and in vitro-produced aS-SALSO species was evaluated on mesencephalic primary neurons from mice. SALSO, under oxidative conditions, stabilizes the monomeric state besides a minor population of oligomers of aS, resulting in a strong inhibition of the fibrillation process. SALSO does not promote any chemical modification of the protein. Instead, the interaction of SALSO with aS seems to occur via hydrophobic effect, likely mediated by the NAC (non-amyloid component) domain of the protein. aS-SALSO species were found to be innocuous on primary neurons, while SALSO alone induces apoptosis via caspase-3 activation. Importantly, exogenous aS monomer was capable of protecting neurons against SALSO toxicity irrespective whether the protein was co-administered with SALSO or added until 2 h after SALSO, as evidenced by DAPI and cleaved-caspase 3 assays. Similar protective action of aS was found by pre-incubating neurons with aS before the administration of SALSO. Interaction of SALSO with aS leads to the formation of fibril-incompetent and innocuous adducts. SALSO toxicity is attenuated by aS monomer. aS could exhibit a protective role against the neurotoxic effects of SALSO in dopaminergic neuron. •SALSO interacts with aS in vitro leading to the stabilization of the protein monomer and small oligomers.•aS-SALSO adducts are fibril-incompetent and innocuous to primary neurons.•SALSO has its toxicity on primary neurons enhanced upon oxidation to SAQ.•SALSO toxicity in neurons is attenuated by the presence of exogenous aS monomer.